Environmental Economics In The Perspective Of Feasibility Study: Integration Of Economic, Social, And Environmental Aspects (Case Study Of The Development Of The Indonesian Ikn) - Erma Widiani; Rosalina Kumalawati (CV. SINAR HOWUHOWU, 2026)
This paper analyzes the feasibility study of Indonesia's new capital city (IKN Nusantara) from a environmental economics perspective. The study integrates economic, social, and environmental dimensions to assess the sustainability of this national project. Using descriptive-qualitative methods, the paper reviews government reports, academic literature, and policy documents related to the IKN development. The findings reveal that economically, the project has potential through investment and regional development, but risks arise if funding from private sectors does not materialize. Socially, the relocation of civil servants and impacts on indigenous communities require inclusive approaches. Environmentally, the project faces high risks such as deforestation, biodiversity loss, and water resource management. Therefore, the feasibility of IKN depends on integrated policies that balance growth, social justice, and ecological sustainability.